2017
DOI: 10.1158/1535-7163.mct-16-0459
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Small-Cell Lung Cancer to Apoptosis Induced by the Combination of BET Bromodomain Proteins and BCL2 Inhibitors

Abstract: Ten percent to 15% of all lung cancers are small-cell lung cancer (SCLC). SCLC usually grows and metastasizes before it is diagnosed and relapses rapidly upon treatment. Unfortunately, no new targeted agent has been approved in the past 30 years for patients with SCLC. The BET (bromodomain and extraterminal) proteins bind acetylated histones and recruit protein complexes to promote transcription initiation and elongation. BET proteins have been shown to regulate expression of key genes in oncogenesis, such as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 38 publications
5
36
1
Order By: Relevance
“…However, additional more detailed studies, for instance in orthotopic xenografts, are necessary to judge the overall impact. Our findings are supported by other groups, showing similar findings in other tumor entities, involving the selective Bcl-2 inhibitor, ABT199 [7, 8] which recently was designated for accelerated FDA approval. All in all, the combination treatment of BH3-mimetics and BET-inhibitors appears to be a potential treatment strategy for several malignancies and should be explored further.…”
supporting
confidence: 91%
“…However, additional more detailed studies, for instance in orthotopic xenografts, are necessary to judge the overall impact. Our findings are supported by other groups, showing similar findings in other tumor entities, involving the selective Bcl-2 inhibitor, ABT199 [7, 8] which recently was designated for accelerated FDA approval. All in all, the combination treatment of BH3-mimetics and BET-inhibitors appears to be a potential treatment strategy for several malignancies and should be explored further.…”
supporting
confidence: 91%
“…In addition, Lam et al very recently reported that venetoclax sensitizes SCLC cell lines to BET inhibition (33). These previous reports support the potential of venetoclax in SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…127 JQ-1 was moreover shown to have antiproliferative effects in SCLC cell lines. 128,129 Interestingly, key targets with reduced expression upon JQ-1 treatment in SCLC cell lines were MYC family members 129 and ASCL1, 130 but currently biomarkers predicting JQ-1 sensitivity in SCLC are lacking. More recently, CHK1 inhibition has been identified as an additional drug target that elicits efficacy specifically in MYCdriven SCLC, 11 suggesting that MYC status is an important determinant of therapeutic response in SCLC.…”
Section: Targeting Myc In Small Cell Lung Cancermentioning
confidence: 99%